An ANP–TOPSIS Multi-Criteria Framework for Carton Packaging Supplier Selection: A Case Study - Ardhy lazuardy; Marsha Aisyaditara (Jurnal Ilmiah Multidisiplin, 2026)
Supplier selection is a strategic decision in supply chain management as it directly affects product quality, operational efficiency, and delivery reliability. In manufacturing industries, carton packaging serves not only as product protection but also as a determinant of perceived quality and customer satisfaction. PT Toa Galva Industries has experienced inconsistencies in carton box quality, leading to disruptions in packaging and distribution processes. This issue highlights the need for a multi-criteria decision-making approach capable of capturing interdependencies among evaluation criteria. This study aims to develop a supplier evaluation and ranking framework for carton packaging using an integrated Analytic Network Process (ANP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) approach. ANP is employed to determine the priority weights of criteria and subcriteria while considering their interrelationships, whereas TOPSIS is applied to rank suppliers based on their closeness to the ideal solution. Data were collected through questionnaires and interviews with experienced procurement and production personnel. The results indicate that quality is the most influential criterion, followed by service, delivery, and cost, with quality consistency identified as the most critical subcriterion. The supplier ranking reveals that PT CTP achieves the highest preference value among the evaluated alternatives. These findings emphasize that quality stability outweighs cost considerations in carton packaging supplier selection. This study contributes practically by providing a structured and objective decision-making framework and academically by extending the application of ANP–TOPSIS in packaging supplier evaluation within manufacturing contexts.